2018
DOI: 10.1002/fsn3.864
|View full text |Cite
|
Sign up to set email alerts
|

Germinated brown rice combined with Lactobacillus acidophilus and Bifidobacterium animalis subsp. lactis inhibits colorectal carcinogenesis in rats

Abstract: Colorectal cancer is a common cancer strongly associated with diet. Certain probiotics and prebiotics possess an inhibitory activity against colorectal cancer, while synbiotics may be more effective in preventing this cancer than either prebiotics or probiotics alone. Germinated brown rice (GBR) is considered as a candidate prebiotics with anticancer potential. However, the effect of GBR combined with probiotics on colorectal cancer is not clear. The present study investigated the preventive effect of combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…After treatment with L. acidophilus (10 9 cfu/day) and dietary fiber (consisting of 90% inulin and 10% oligofructose) for four weeks, the content of L. acidophilus in the feces was significantly increased compared to the placebo group, which confirmed that synbiotics can modulate the intestinal microflora [43]. A preliminary study in our laboratory demonstrated that the combination of probiotic L. acidophilus and germinated brown rice rich in dietary fiber suppressed DMH/DSS-induced colonic precancerous lesions via regulation of antioxidation and apoptosis in rats [44]. These findings suggest that such a synbiotic combination may be a potential functional food or chemopreventive agent for the control of CRC [44].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…After treatment with L. acidophilus (10 9 cfu/day) and dietary fiber (consisting of 90% inulin and 10% oligofructose) for four weeks, the content of L. acidophilus in the feces was significantly increased compared to the placebo group, which confirmed that synbiotics can modulate the intestinal microflora [43]. A preliminary study in our laboratory demonstrated that the combination of probiotic L. acidophilus and germinated brown rice rich in dietary fiber suppressed DMH/DSS-induced colonic precancerous lesions via regulation of antioxidation and apoptosis in rats [44]. These findings suggest that such a synbiotic combination may be a potential functional food or chemopreventive agent for the control of CRC [44].…”
Section: Discussionsupporting
confidence: 57%
“…A preliminary study in our laboratory demonstrated that the combination of probiotic L. acidophilus and germinated brown rice rich in dietary fiber suppressed DMH/DSS-induced colonic precancerous lesions via regulation of antioxidation and apoptosis in rats [44]. These findings suggest that such a synbiotic combination may be a potential functional food or chemopreventive agent for the control of CRC [44]. Meanwhile, the present study proved that the combination of djulis and a high dose of L. acidophilus improved DMH/DSS-induced reduction of L. acidophilus in feces.…”
Section: Discussionmentioning
confidence: 98%
“…e supplementation of probiotics and GBR protects the CRC rat by increasing the expression of p53, Bax, caspase-3, and Bax/Bcl-2 ratio and restored the SOD activity. e results suggested that GBR and probiotic supplementation improved the antioxidant machinery of the host system and induced the apoptosis in tumor cells [49].…”
mentioning
confidence: 94%
“…Lin et al [49] revealed that the supplementation of L. acidophilus LA5 and/or B. animalis subsp. lactis BB-12 (5 × 10 7 CFU of single probiotic strain/day or 2.5 × 10 7 CFU each strain/day) and germinated brown rice extract (GBR; 10% in diet) for 10 weeks reduced the mucin-depleted foci formation, ACF-producing sialomucin and expression of anti-apoptotic Bcl-2 in azoxymethane/dextran sodium sulfate-induced CRC rat model.…”
mentioning
confidence: 99%
“…Some of the reported beneficial effects of probiotics in human health include anticancer [99][100][101][102][103][104][105][106][107][108][109][110][111], anti-allergic [112,113], anti-diabetic [114][115][116], anti-obesity [117][118][119][120], anti-pathogenic [121,122], immunomodulatory [123], and anti-inflammatory [124][125][126][127] activities [128], as reported in Table 1.…”
Section: Health Promoting Effect Of Prebiotics Probiotics and Synbimentioning
confidence: 99%